Cardiac implantable electronic devices: a marker for poor outcome in patients with COVID-19 infection. (14th October 2021) - Wizman, B; Haim, M; Yasoor, N; Peles, I; Novack, V; Konstantino, Y; ,
Abstract: Background: A high percentage of SARS-CoV-2 patients suffer from comorbidities and there is increasing evidence that previous cardiac disease contributes to poor outcome in these patients (1, 2). There is a paucity of information regarding the implications of the disease in patients with cardiac implantable electronic devices (CIEDs). Due to the increasing use of CIEDs in the management of arrhythmias and heart failure, determining the association between CIEDs and the severity of this disease is essential. Aim: To obtain an adequate understanding regarding the association between cardiac devices and severity of COVID-19 infection in order to achieve optimum management of these patients. Methods: All clinical and demographic parameters were collected retrospectively from a cohort of patients who underwent implantation of CIED in our Medical Center, Israel. We included 42 patients who tested positive for SARS-CoV-2, between January and December of 2020. Propensity score matching based on age and gender and adjusted Kaplan Meier curve of mortality were performed in order to evaluate the clinical outcome of patients with CIEDs and SARS- CoV-2 infection in comparison to the control group. Results: The mean age of patients was 72.9 years, compose of 50% male and 50% female in both groups. In the group of patients with CIEDs, 11 (26.1%) patients had implantable defibrillator, and 31 (73.8%) had pacemaker. Univariate analysis revealed that patients with CIEDs suffered more from heart failure, coronary artery disease and atrial fibrillation, as well as hypertension, diabetes, and chronic kidney disease. Four patients (9.5%) with cardiac devices were hospitalized in the ICU due to critical illness, as compared to 1 (0.6%) patient in the control group (p=0.005). Moreover, 10 patients in the cardiac devices group (23.8%) died of SARS-CoV-2 infection, versus 25 (14.9%) in the control group. Conclusions: CIEDs are a marker of poor outcome in patients with SARS-CoV-2 infection. Patients with CIEDs suffer from increased comorbidities in comparison with age and gender matched population and therefore should be managed with the utmost caution. Funding Acknowledgement: Type of funding sources: None.